1995
DOI: 10.1152/ajpheart.1995.268.2.h703
|View full text |Cite
|
Sign up to set email alerts
|

CaMKII is responsible for activity-dependent acceleration of relaxation in rat ventricular myocytes

Abstract: We investigated the role of Ca/calmodulin-dependent protein kinase (CaMKII) in relaxation and cytosolic free [Ca] ([Ca]i) decline during steady-state (SS) and postrest (PR) twitches in intact rat ventricular myocytes. Half-time of mechanical relaxation and time constant of [Ca]i decline (tau) were twofold greater during PR than with SS at 1 Hz. This difference was 1) abolished by inhibition of sarcoplasmic reticulum (SR) Ca accumulation by thapsigargin or caffeine; 2) greater at higher stimulation frequency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
98
2
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(120 citation statements)
references
References 0 publications
15
98
2
5
Order By: Relevance
“…Both relaxation and [Ca 2+ ] i decline rates are accelerated at higher frequency in all species studied and enhanced rate of SR Ca 2+ uptake appears to drive both effects [9][10][11][12]. Some reports have shown that FDAR can be strongly suppressed by CaMKII inhibitors (KN-93, KN-62, AIP) [9,[12][13][14], while other reports could not detect effects on FDAR of organic inhibitors or KN-62 [11,[15][16][17]. CaMKII-dependent PLB phosphorylation seemed a plausible FDAR mediator and some data seemed to support that [14,18].…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Both relaxation and [Ca 2+ ] i decline rates are accelerated at higher frequency in all species studied and enhanced rate of SR Ca 2+ uptake appears to drive both effects [9][10][11][12]. Some reports have shown that FDAR can be strongly suppressed by CaMKII inhibitors (KN-93, KN-62, AIP) [9,[12][13][14], while other reports could not detect effects on FDAR of organic inhibitors or KN-62 [11,[15][16][17]. CaMKII-dependent PLB phosphorylation seemed a plausible FDAR mediator and some data seemed to support that [14,18].…”
Section: Introductionmentioning
confidence: 86%
“…The contribution of PLB and CaMKII to FDAR remains controversial. CaMKII inhibition has been reported to suppress FDAR in several studies [9,12,13], but other studies did not detect FDAR inhibition with KN-93 or KN-62 [11,[15][16][17]. In isolated myocytes CaMKII dependent phosphorylation of PLB at Thr17 occurs in a frequency dependent manner [14,17].…”
Section: Fdar and Cytosolic Ca 2+ Removalmentioning
confidence: 98%
See 1 more Smart Citation
“…FDAR ensures appropriate ventricular filling at high heart rates, and results from accelerated SR Ca 2+ uptake independent of Ca 2+ removal out of the cell [27]. However, the contributions of PLB and CaMKII to FDAR remain controversial [28].…”
Section: Frequency-dependent Acceleration Of Relaxation (Fdar)mentioning
confidence: 99%
“…A growing body of evidence has demonstrated that CaMKII can also be activated by ROS 21, 22, 23, 24. Once activated, CaMKII can phosphorylate a wide range of key Ca 2+ and Na + regulatory proteins such as LCCs,25, 26, 27, 28 RyRs,29, 30, 31, 32, 33, 34, 35 phosphalamban,29, 34, 36 and Na + channels 37, 38. Importantly, Xie et al39 showed that H 2 O 2 perfusion–induced oxidative CaMKII activation leads to afterdepolarizations in isolated rabbit cardiomyocytes, likely by phosphorylation of Na + channels and LCCs.…”
Section: Introductionmentioning
confidence: 99%